Journey into Buddhism. Dharma River [videorecording (DVD)] (Bush, John (Filmmaker) Yatra series., 2007)
Journey through legendary rivers to the greatest Buddhist temples and mystical sites of Laos, Thailand, and Burma. Explore the different cultural representations of this universal icon of inner peace.